Pengaruh Strategi Pembelajaran Aktif Video Kritik Terhadap Perhatian Dan Hasil Belajar Peserta Didik Pada Materi Pelajaran Pemanasan Global - RACHMAWATI RACHMAWATI; LEONARDO ELISA AISOI (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2020)
The aim of this study was to find out (1) To know the influence of active learning strategy video critic to students’ attention on the subject material global warming in grade VII of SMP Muhammadiyah Jayapura. (2). To know the influence of active learning strategy video critic to students’ learning result on the subject material global warming in grade VII of SMP Muhammadiyah Jayapura. The kind of the research is quantitative.The research design used is Quasi Experimental Design in the form of Nonequivalent Control Group Design. The population is all students grade VII of SMP Muhammadiyah Jayapura. The taking of sample is conducted with the technique of purposive sampling. And class VII D as the class control and VII D as class experiment. The instruments used are survey, observation, and objective test questions. The data is analyzed with the simple regression test. The result of the researchshows that : (1) There is significant influence to students’s attention in following learning process by using active learning strategy of video critic with the score of is bigger than (2,90>2,045). (2) There is significant influence between the students’ learning result in the class experiment by using the active learning strategy video critic with the score of is bigger than ( 2,292>2,045).